Evaluation of New Product Development Process and Organization A case study of connected solutions company - Jeong, Hyejin (My University, 2023)
Customer needs have been changed to experience products as early as possible with similar or even higher quality products than in the past. Therefore, to align with customer needs, firms' way of working has changed significantly to increase their velocity and flexibility when developing products. However, since the way of working is closely related to new product development (NPD) processes and organizations, merely changing the way of working cannot meet customer needs. Therefore, these three aspects should be considered when tailoring NPD processes. The case company's way of working is continuously evolving to increase not only product quality but also efficiency by adopting a Scaled Agile Framework (SAFe) to meet customers' expectations through its NPD process. However, it is important to evaluate whether the current way of working, the NPD process, and the organization are closely managed together. However, the case company raises the need to evaluate the current way of working, the NPD process, and whether the organization is closely managed together, and to find potential improvements to meet customer needs. Therefore, this study was conducted according to the request of the case company. Mixed research combining qualitative and quantitative approaches was adopted to evaluate the current situation of the case company. The primary source of the research is a qualitative approach that is in line with interviews and literature reviews, and the quantitative approach supports findings based on a qualitative approach. The purpose of conducting quantitative research, which is a survey and a self-completion questionnaire, was to investigate employees’ perceptions. The self-completion questionnaire was aimed at evaluating the current SAFe maturity level in the case study. After analyzing the data, two benchmarks were conducted to gain ideas about how other companies are dealing with the challenges faced by the case company. The study identified three categories of challenges: process-related, organizational-related, and knowledge management-related challenges. Furthermore, root cause analysis was conducted to determine where the challenges derived from the three categories of challenges, and the identified root causes are the inflexible NPD process, late risk management, decentralization, lack of customer involvement, and lack of knowledge management. Therefore, recommendations are based on aiming to decrease time-to-market and increase product quality to overcome the identified challenges, since time and quality are perceived as the most important factors when developing a new product at the case company.
Keywords: New Product Development (NPD) process; Scaled Agile Framework (SAFe); Agile process; Process tailoring; Agile testing; Capability Maturity Model Integration (CMMI); Centralization; Decentralization; Ambidexterity; Formalization; Knowledge Management